(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The Organisation Internationale de la Francophonie (OIF) has traditionally been presented as a vehicle for cultural cooperation and linguistic promotion. This paper argues that under the presidencies of François Hollande and, more decisively, Emmanuel Macron, the institution and the broader concept of Francophonie have been strategically reconfigured into a tool of neo-mercantilist policy in Africa. Faced with intensified global competition from China, Russia, and Turkey, and a rising wave of anti-French sentiment in its traditional spheres of influence, France has undertaken a deliberate discursive and strategic shift. This paper employs critical discourse analysis to trace the evolution of French official rhetoric, identifying a systematic move away from the lexicon of “coopération” and “rayonnement” (cultural influence) towards a new vocabulary of “partenariats économiques,” “écosystèmes d’affaires,” and “Francophonie économique.” Concurrently, it analyzes policy documents and financial flows to demonstrate how this discourse is operationalized through development aid, investment treaties, and diplomatic initiatives. The findings reveal that the Francophonie économique is not merely a supplementary economic dimension but a fundamental reorientation of French foreign policy. It represents an attempt to leverage linguistic and historical ties to secure market access, promote French corporate interests, and maintain geopolitical relevance in a multipolar world, thereby masking a realist pursuit of power within a neoliberal and cooperative discursive framework.